2007
DOI: 10.1021/jf0703304
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins in Wild Blueberries of Quebec:  Extraction and Identification

Abstract: Anthocyanins were extracted from a mixture of berries of Vaccinium angustifolium and Vaccinium myrtilloïdes at 7.7 degrees C, 26 degrees C, and 79 degrees C using ethanol alone or ethanol acidified with hydrochloric, citric, tartaric, lactic, or phosphoric acids at a solvent to solid ratio of 10. The effect of these parameters on extracted anthocyanins stability was investigated. The pH-differential and HPLC-DAD methods were used to determine anthocyanin contents. Extracted anthocyanins were purified on a C-18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
122
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 24 publications
7
122
1
2
Order By: Relevance
“…Yet, the reverse situation has also been reported [62]. Although the pH differential method versus LC analyses can deliver differing results from the same sample, blueberry data tend to be closely correlated, which indicates that both approaches are reliable [60,61,63]. The loss to press cake is similar to the percentages found in the literature [19,37].…”
Section: Individual Anthocyanidinssupporting
confidence: 52%
“…Yet, the reverse situation has also been reported [62]. Although the pH differential method versus LC analyses can deliver differing results from the same sample, blueberry data tend to be closely correlated, which indicates that both approaches are reliable [60,61,63]. The loss to press cake is similar to the percentages found in the literature [19,37].…”
Section: Individual Anthocyanidinssupporting
confidence: 52%
“…Mixed well and also allow those compounds for 15 min to absorb measurements on spectrophotometer at 500 nm and 700 nm (Nicoue et al, 2007). Distilled water used for blank purpose.…”
Section: Anthocyaninsmentioning
confidence: 99%
“…According to Nicoué et al (2007), co-elutions are common in reverse-phase liquid chromatography analysis of anthocyanins in blueberries because they contain a complex mixture of such compounds, and it is only possible to detect and distinguish these compounds by mass spectroscopy. Kalt et al (1999) identified 25 peaks representing simple or acylated anthocyanins in different species of blueberry, with delphinidin as the major compound.…”
Section: Anthocyaninsmentioning
confidence: 99%